Outline for a course in domestic science: to be used in the schools of New Bedford, Massachusetts - Willis, Clara (My University, 1908)
Introduction: Vacation Schools. Life Among the Mill Operatives. The problem of taking care of the children of the poor and helping them during the summer months becomes one of the utmost interest in large cities. It is met, in part, by the vacation schools, which hold during six months or more in the most thickly settled and miserable parts of the large milling cities.
Citation: Willis, Clara. Outline for a course in domestic science: to be used in the schools of New Bedford, Massachusetts. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Domestic Science; Home Economics; Education; Massachusetts; Graduating theses; Senior theses; Theses